2004
DOI: 10.1073/pnas.0402114101
|View full text |Cite
|
Sign up to set email alerts
|

O 2 activation by binuclear Cu sites: Noncoupled versus exchange coupled reaction mechanisms

Abstract: Binuclear Cu proteins play vital roles in O2 binding and activation in biology and can be classified into coupled and noncoupled binuclear sites based on the magnetic interaction between the two Cu centers. Coupled binuclear Cu proteins include hemocyanin, tyrosinase, and catechol oxidase. These proteins have two Cu centers strongly magnetically coupled through direct bridging ligands that provide a mechanism for the 2-electron reduction of O2 to a -2 : 2 side-on peroxide bridged Cu II 2 (O 2 2؊ ) species. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
148
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 36 publications
3
148
0
1
Order By: Relevance
“…Cu H as an ET Site. The lack of exchange coupling between Cu H and Cu M has been explained as the key factor directing the reactivity of the noncoupled binuclear copper enzymes toward 1e -HAA/ hydroxylation, as opposed to 2e -electrophilic aromatic attack in the coupled binuclear Cu enzymes (32). This control allows the overall two-electron oxidation of substrate to be accomplished by delivering electrons to the active Cu M site one at a time, which permits one-electron reduction of O 2 to the superoxide intermediate to "turn on" substrate HAA rather than two-electron reduction of O 2 to a (hydro)peroxo intermediate that is not activated toward HAA.…”
Section: Discussionmentioning
confidence: 99%
“…Cu H as an ET Site. The lack of exchange coupling between Cu H and Cu M has been explained as the key factor directing the reactivity of the noncoupled binuclear copper enzymes toward 1e -HAA/ hydroxylation, as opposed to 2e -electrophilic aromatic attack in the coupled binuclear Cu enzymes (32). This control allows the overall two-electron oxidation of substrate to be accomplished by delivering electrons to the active Cu M site one at a time, which permits one-electron reduction of O 2 to the superoxide intermediate to "turn on" substrate HAA rather than two-electron reduction of O 2 to a (hydro)peroxo intermediate that is not activated toward HAA.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Buffers are invariably used in the sample storage and analysis process. It is widely known that the pH of a buffer solution can change at low temperatures, and this has been ascribed to enthalpic effects on the proton equilibrium as well as selective precipitation of buffer components upon cooling.…”
mentioning
confidence: 99%
“…This experimental finding contradicts the mechanism suggested by Crespo et al (21), because a very small energy barrier does not lead to a significant KIE. Klinman and co-workers (10,25) suggested a Cu(II)-superoxo mechanism, similar to the one proposed by Solomon and co-workers (19,20), based on experimental indications but without computational backup. Based on recent QM/MM calculations (12), it was argued that the high barrier for the Cu(II)-superoxo case is a spurious effect of the lack of relaxation of the solvent.…”
mentioning
confidence: 65%
“…Prigge et al (7) suggested Cu M ϩ -O 2 Ϫ 7 Cu M 2ϩ -O 2 2Ϫ as the abstracting species based on the crystal structure. Gas phase density functional theory calculations with a truncated model of the protein by Chen and Solomon (19,20) suggested a Cu(II)-superoxo species to be responsible for the abstraction of the glycine hydrogen. This mechanism was ruled out by Crespo et al (21) because including the environment of the protein in a QM/MM fashion enlarged the energy barrier up to 84 kJ mol Ϫ1 (gas-phase calculations by Chen and Solomon (19,20) gave a value of ϳ60 kJ mol Ϫ1 for the energy barrier).…”
mentioning
confidence: 99%
See 1 more Smart Citation